Crash Culpability Relative to Age and Sex for Injured Drivers Using Alcohol, Marijuana or Cocaine - Soderstrom, Carl A. (Association for the Advancement of Automotive Medicine, 2005)
While there is a great deal of data documenting the etiologic role alcohol use plays in crash culpability, there is a dearth of data for other drugs. The purpose of this study was to assess crash culpability for single drug use among injured drivers admitted to a regional trauma center. This study is the largest of its kind involving trauma center patients. Clinical toxicology results obtained for patient care were linked to police crash reports containing a field attributing crash culpability. Drugs studied were alcohol, cocaine, and marijuana. As expected crash culpability was strongly associated with pre-crash alcohol use. In contrast, for both men and women, this study did not find an association between crash culpability and marijuana use. The data documents a significant association between cocaine use and crash culpability for both sexes and for drivers 21 to 40 years of age. This is the first large study to assess for crash culpability among injured drivers relative to cocaine use.